Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Keterampilan Proses Sains dan Hasil Belajar IPA Siswa - Elyas Djufri; Trio Ardhian (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2021)
This research aims to investigate the effect of guided inquiry learning model upon scienific attitude and science learning achievement which uses the posttest-only control group design. This research is conducted at fourth grade students of SD Negeri Kecamatan Galang. The reseach population are 125 students samples are 64 students. Data of scientific attitude was collected by using observationmethod, and the data of science learning achievement was collected by using test method. The data was analyzed using SPSS 20.00 for windows bases MANOVA. The rsults show that: (1) there are significant differences of science process skill and science learning achievement between student studying by using guided inquiry learning model and conventional learning model (p<0.05), (2) There is significant difference of science process skill between student studying by using guided inquiry learning model and conventional learning model (p<0.05), (3) There is significant difference of science learning achievement between student studying by using guided inquiry learning model and conventional learning model (p<0.05)